2022
DOI: 10.1039/d2re00044j
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the kinetics of 4-nitrophenol reduction by NaBH4 in the presence of Ag and Au nanoparticles

Abstract: The reduction of 4-nitrophenol (4-NiP) to 4-aminophenol (4-AP) with an excess of sodium borohydride is commonly used as a model reaction to assess the catalytic activity of metallic nanoparticles. This...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…As illustrated in Figure , when the 4-NP reduction was performed in the presence of 10% IPA, only 5% of 4-NP was reduced, compared to 94% degradation in the reaction without IPA. It has previously been shown that the reduction kinetics is strongly affected by the presence of alcohol in the reaction medium . This study further corroborated other works showing that the hydroxyl radical is indeed the major reducing agent in the reduction of 4-NP to 4-AP.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As illustrated in Figure , when the 4-NP reduction was performed in the presence of 10% IPA, only 5% of 4-NP was reduced, compared to 94% degradation in the reaction without IPA. It has previously been shown that the reduction kinetics is strongly affected by the presence of alcohol in the reaction medium . This study further corroborated other works showing that the hydroxyl radical is indeed the major reducing agent in the reduction of 4-NP to 4-AP.…”
Section: Resultssupporting
confidence: 90%
“…To ascertain the role of hydroxyl radical requirement for the catalytic reduction mechanism, an oxidizing agent, IPA, was used as a scavenger . As illustrated in Figure , when the 4-NP reduction was performed in the presence of 10% IPA, only 5% of 4-NP was reduced, compared to 94% degradation in the reaction without IPA.…”
Section: Resultsmentioning
confidence: 99%
“…Since reduction of nitrophenol using NaBH 4 is an electron transfer process, solvent polarity plays a significant role in catalytic reduction of nitrophenols. Hughes-Ingold rules state a simple solvation model where electrostatic interactions take place between the initial and transition states of the dissolved molecules, solvent polarity increases the rate of reduction due to the formation of a charged species . Methanol with a nonpolar methyl group has much lower polarity as compared to water; hence, in the presence of methanol the reduction rate decreases to a great extent.…”
Section: Resultsmentioning
confidence: 99%
“…Hughes-Ingold rules state a simple solvation model where electrostatic interactions take place between the initial and transition states of the dissolved molecules, solvent polarity increases the rate of reduction due to the formation of a charged species. 61 Methanol with a nonpolar methyl group has much lower polarity as compared to water; hence, in the presence of methanol the reduction rate decreases to a great extent. Further, due to its bulky nature, tert-BuOH decreased the H donor ability and delayed the charge transfer process to the nitro compounds thereby reducing the rate of reduction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With the rapid development of industry, the discharge of dyeing wastewater has become a serious environmental problem. 1,2 The main components of dyeing wastewater are regarded as nitro and azo compounds [e.g., 2-nitrophenol (2-NP), 3-nitrophenol (3-NP), 4-nitrophenol (4-NP), methyl red (MR) and methyl orange (MO)], which can result in severe damage to ecosystems and human health because of their strong toxicity, carcinogenicity and teratogenicity. 3,4 Unfortunately, owing to their high photothermal stability and resistance to biodegradability, it is difficult to completely remove these pollutants using conventional methods (e.g., biological degradation, adsorption and extraction).…”
Section: Introductionmentioning
confidence: 99%